Penggunaan Color Palette Postingan Instagram @Muspera Kehutanan dalam Meningkatkan Brand Awareness Museum dan Perpustakaan Kehutanan - Azzahra Pramesti Ashari; Wahyu Budi Priatna (Lembaga Pengembangan Kinerja Dosen, 2025)
The Use of Color Palette Instagram Posts @muspera_kehutanan in Increasing Brand Awareness of the Forestry Museum and Library seeks to investigate in depth the role of color palettes in efforts to raise brand awareness of the Ir. Djamaludin Suryohadikusumo Forestry Museum and Library on Instagram social media @muspera_kehutanan. This study used a descriptive qualitative approach with four levels of Brand Awareness: Recognition Level, Recall Level, Brand Association, and Top of Mind. This study found that using consistent color palettes on the @muspera_kehutanan Instagram account helps to increase brand awareness for the Ir. Djamaludin Suryohadikusumo Forestry Museum and Library. Although it has not reached the forefront of people's minds, the strategic initiatives made have laid a solid foundation for long-term reach expansion and audience loyalty.